Preassembly of specific Gβγ subunits at GABAB receptors through auxiliary KCTD proteins accelerates channel gating - Fritzius, Thorsten; Tureček, Rostislav; Fernandez-Fernandez, Diego; Isogai, Shin; Rem, Pascal D; Kralikova, Michaela; Gassmann, Martin; Bettler, Bernhard (Biochemical pharmacology, 2024)
GABAB receptors (GBRs) are G protein-coupled receptors for GABA, the main inhibitory neurotransmitter in the brain. GBRs regulate fast synaptic transmission by gating Ca2+ and K+ channels via the Gβγ subunits of the activated G protein. It has been demonstrated that auxiliary GBR subunits, the KCTD proteins, shorten onset and rise time and increase desensitization of receptor-induced K+ currents. KCTD proteins increase desensitization of K+ currents by scavenging Gβγ from the channel, yet the mechanism responsible for the rapid activation of K+ currents has remained elusive. In this study, we demonstrate that KCTD proteins preassemble Gβγ at GBRs. The preassembly obviates the need for diffusion-limited G protein recruitment to the receptor, thereby accelerating G protein activation and, as a result, K+ channel activation. Preassembly of Gβγ at the receptor relies on the interaction of KCTD proteins with a loop protruding from the seven-bladed propeller of Gβ subunits. The binding site is shared between Gβ1 and Gβ2, limiting the interaction of KCTD proteins to these particular Gβ isoforms. Substituting residues in the KCTD binding site of Gβ1 with those from Gβ3 hinders the preassembly of Gβγ with GBRs, delays onset and prolongs rise time of receptor-activated K+ currents. The KCTD-Gβ interface, therefore, represents a target for pharmacological modulation of channel gating by GBRs.
Keywords: GTP-Binding Protein gamma Subunits; Ion Channel Gating; HEK293 Cells; G protein; Receptors, GABA-B; proteiny vázající GTP - beta-podjednotky; proteiny vázající GTP - gama-podjednotky; Xenopus laevis; GABA(B); GTP-Binding Protein beta Subunits; receptory GABA-B; zvířata; HEK293 buňky; Humans; GIRK channel; Potassium Channels; GPCR; draslíkové kanály; gating iontového kanálu; KCTD; lidé; Animals